Pendampingan Penulisan Artikel Ilmiah Hasil KKN/PLP Bagi Mahasiswa Pendidikan Fisika di Universitas Pendidikan Mandalika - Herayanti, Lovy; Gummah, Syifa’ul; Sukroyanti, Baiq Azmi; Ahzan, Sukainil; Fuaddunnazmi, M.; Hariyanti, Padiya; Mahni, Mahni (Indonesian Publication Center, 2024)
Scientific publication is crucial in academia, yet many Physics Education students struggle to convert their Community Service Program (KKN) or School Field Introduction (PLP) reports into quality scientific articles due to substantive, technical, and procedural challenges. This study aims to enhance students' scientific writing competence through intensive mentoring. The mentoring method involved four stages: socialization and preparation, a writing workshop on the IMRaD format, a manuscript clinic with peer-review and one-on-one guidance (including the use of reference managers like Mendeley for citation and paraphrasing), and submission assistance via the Open Journal System (OJS). The results show a significant improvement in the quality of article drafts, especially the abstract and introduction, and students' ability to construct analytical-argumentative discussions. The one-on-one coaching method proved effective in providing direct feedback. Students also became proficient in operating reference managers and understanding the OJS publication process, enhancing their digital literacy and academic confidence. This program successfully facilitated the transformation of KKN/PLP reports into publishable scientific works, fostering a sustainable writing culture, and improving the profile of academically literate graduates.